Transnasal endoscopic resection of Epstein-Barr virus–associated cavernous sinus tumour. Issue 10 (30th October 2020) - Yokoyama, Daiki; Horiguchi, Kentaro; Higuchi, Yoshinori; Hashiba, Jun
Abstract : Epstein-Barr virus–associated smooth muscle tumour (EBV-SMT) is a rare disease occurring in immunosuppressed patients, such as those with AIDS, post-transplantation immunodeficiency and congenital immunodeficiency. Intracranial EBV-SMT after solid organ transplantation has been reported. However, intracranial lesions after bone marrow transplantation are extremely rare. We report the case of a 47-year-old man with a history of acute myeloid leukaemia and bone marrow transplantation. He had symptoms of trigeminal neuralgia, and MRI revealed a left cavernous sinus tumour. He started taking oral gabapentin, but his symptoms did not improve. We performed transnasal endoscopic surgery. Postoperative MRI showed complete removal of the cavernous sinus lesion. Pathological examination showed spindle-shaped cells positive for smooth muscle markers and EBV-encoded small RNA in situ hybridisation. EBV-SMT was pathologically diagnosed. His symptoms improved after surgery. No tumour recurrence was noted on follow-up MRI after 15 months without adjuvant radiation or chemotherapy.